2019
DOI: 10.3390/biom9010023
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Molecular Applications of Recent Developments in Optical Tweezers

Abstract: In the past three decades, the ability to optically manipulate biomolecules has spurred a new era of medical and biophysical research. Optical tweezers (OT) have enabled experimenters to trap, sort, and probe cells, as well as discern the structural dynamics of proteins and nucleic acids at single molecule level. The steady improvement in OT’s resolving power has progressively pushed the envelope of their applications; there are, however, some inherent limitations that are prompting researchers to look for alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
65
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 111 publications
0
65
0
1
Order By: Relevance
“…High-intensity femtosecond lasers provide a plethora of applications reaching from ultrafine material processing 45 , highprecision medical surgery 46 , to the detection of biomolecular processes 47 . In the search for effective cross-linking methods of proteins and DNA, we and others have previously shown that femtosecond lasers are promising for this purpose because they provide high cross-linking yields while minimizing DNA damage 20,24,48,49 .…”
Section: Discussionmentioning
confidence: 99%
“…High-intensity femtosecond lasers provide a plethora of applications reaching from ultrafine material processing 45 , highprecision medical surgery 46 , to the detection of biomolecular processes 47 . In the search for effective cross-linking methods of proteins and DNA, we and others have previously shown that femtosecond lasers are promising for this purpose because they provide high cross-linking yields while minimizing DNA damage 20,24,48,49 .…”
Section: Discussionmentioning
confidence: 99%
“…After nearly 50 years of development, optical trapping and manipulation via COTs have made great progresses in both methods and applications, with manipulated samples ranging from different dielectric particles to biological cells and biomolecules [4,5]. However, a high numerical aperture (NA) objective is necessary for the light focusing via COTs.…”
Section: Introductionmentioning
confidence: 99%
“…Since the development of optical tweezers in 1986 by Ashkin [1], this trapping technique has been used for numerous applications including the manipulation of microscopic organisms [2][3][4], nanoparticles [5] and quantum dots [6]. By now, optical tweezers have become a standard, non-invasive tool exploiting optical forces, typically in the pico or femtonewton range, for trapping and manipulating small objects by exerting a highly focused laser beam through a high numerical aperture (NA) objective [7].…”
Section: Introductionmentioning
confidence: 99%